MICROSTRUCTURAL EVOLUTION AND TENSILE BEHAVIOR OF DISSIMILAR STEEL JOINTS UNDER MULTI-PASS WELDING - Saripuddin M; Li Wei; Zhang Li (Yayasan Adra Karima Hubbi, 2026)
Dissimilar steel joints are increasingly employed in demanding engineering structures, yet repeated thermal cycles during multi-pass welding can generate complex microstructural heterogeneity and localized mechanical-property gradients that affect structural integrity. This study investigates the relationship between cumulative welding thermal history, microstructural evolution, local property variation, and tensile fracture behavior in multi-pass dissimilar steel joints. An experimental laboratory design integrated controlled multi-pass welding, metallographic characterization, microhardness mapping, transverse tensile testing, fracture-location analysis, and fractographic examination to establish process–structure–property relationships. The results revealed pronounced microstructural and hardness variations across the weld metal, fusion boundaries, heat-affected zones, and base materials due to unequal thermal histories and repeated reheating. Tensile fracture occurred preferentially within or adjacent to mechanically heterogeneous transition regions rather than consistently within the weld centerline or maximum-hardness zone, demonstrating the critical influence of local strength–ductility mismatch and deformation compatibility. The study concludes that tensile performance cannot be adequately explained by average strength or peak hardness alone. An integrated pathway linking thermal history, microstructural evolution, property gradients, strain localization, and fracture behavior provides a stronger mechanistic framework for evaluating joint integrity and optimizing multi-pass welding procedures for reliable dissimilar steel structures under demanding industrial service conditions.